2012
DOI: 10.1007/s13258-011-0148-4
|View full text |Cite
|
Sign up to set email alerts
|

TSLPR gene polymorphism is associated with systemic lupus erythematosus in the Korean population

Abstract: Human thymic stromal lymphopoietin receptor (TSLPR) was identified from T lymphocytes and dendritic cells, and is believed to play an important role in the development of inflammatory and allergic responses. We previously identified 11 single-nucleotide polymorphisms (SNPs) and 2 variation sites in the TSLPR gene, and showed that SNPs in the TSLPR gene are associated with susceptibility to atopic asthma in the Korean population. The present study aimed to investigate whether polymorphisms in the TSLPR gene are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Consistent with previous studies, TSLPR gene polymorphisms were found to be correlated with increased susceptibility to atopic asthma in the Korean population( Yu et al, ) and with systematic lupus erythematous( Yu, Chun, Yun, Moon, & Chae, ). However, although several SNPs in IL7R have been associated with a wide range of diseases like liver disease in HIV/HCV infected patients (Guzmán‐Fulgencio et al, ) and sclerosis risk (Wu et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous studies, TSLPR gene polymorphisms were found to be correlated with increased susceptibility to atopic asthma in the Korean population( Yu et al, ) and with systematic lupus erythematous( Yu, Chun, Yun, Moon, & Chae, ). However, although several SNPs in IL7R have been associated with a wide range of diseases like liver disease in HIV/HCV infected patients (Guzmán‐Fulgencio et al, ) and sclerosis risk (Wu et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…SNPs in the signal transducer and activator of transcription 4 gene are associated with nephritis, as well as double stranded DNA autoantibodies in SLE patients, 16 with accumulating reports also signifying that these SNPs are associated with clinical features of SLE. [17][18][19] We previously reported that rs1044856 and rs1359184 in EPSTI1 are associated with elevated ESR and ANA levels in SLE patients, respectively, 11 and also that SNPs in the Forkhead-box J1, 20 interleukin coactosin-like 1, 21 thymic stromal lymphopoietin receptor, 22 GABRP, 10 and EPSTI1 genes 11 are associated with SLE susceptibility in the Korean population. In the present study, we evaluated the association between BMP6 polymorphisms and SLE susceptibility.…”
Section: Discussionmentioning
confidence: 96%
“…Management of this disease is complex and usually involves many different specialties for optimal patient management [ 11 ]. We previously reported that SNPs in the forkhead-box J1 ( FOXJ1 ), interleukin coactosin-like 1 ( COTL1 ), and thymic stromal lymphopoietin receptor ( TSLPR ) genes are associated with susceptibility to SLE in a Korean population [ 12 14 ]. In this study, we evaluated the association between GABRP polymorphisms and susceptibility to SLE.…”
Section: Discussionmentioning
confidence: 99%